Progress Report on the Activities of the Independent Evaluation Office. (Policy Papers; Policy Paper, 2011)
Since its last report in October 2010, the Independent Evaluation Office (IEO) has completed its evaluation of IMF Performance in the Run-Up to the Financial and Economic Crisis: IMF Surveillance in 2004-07 and has begun work on two new evaluations. The IEO expects to submit its evaluation of Research at the IMF: Relevance and Utilization to the Executive Board shortly.